Growth and structural property studies on NiSi/SiC core-shell nanowires by hot-wire chemical vapor deposition - Nazarudin, N.F.F.; Azizan, S.N.A.; Rahman, S.A.; Goh, B.T. (Elsevier, 2014)
NiSi/SiC core-shell nanorods and nanowires grown on Ni-coated glass substrates by hot-wire chemical vapor deposition were studied. Nickel was used as a catalyst to induce the growth of these core-shell nanorods and nanowires at deposition pressures varying from 100 to 300 Pa. Increase of the deposition pressure to 300 Pa result in the growth of nanowires. These nanowires consisted of single crystalline NiSi and amorphous SiC as core and shell of the nanowires, respectively. Moreover, an increase in deposition pressure induces phase transition of the nanowires from the crystalline Si phase to amorphous SiC phase. 3C-SiC nano-crystallites embedded within anamorphous matrix were present in the nanowires shells, and broad photoluminescencee mission spectra were observed within the visible region. The effects of the deposition pressure on the growth and structural properties of these core-shell nanowires are discussed.